Estratégias de emancipação: tecendo identidades e metamorfoses no estado de exceção - Ferreira, Ana Caroline Silva (Universidade do Vale do Rio dos Sinos, 2013)
This study analyzes the process of identity constitution among egresses of the penitentiary system in tuberculosis treatment. It is believed that the choice of such theme provides further discussions on the issue of TB in prisons and the creation of stigmas on the identity and recognition of egresses, as it helps to understand the political, ideological, and subjective factors implicated in the formation of the identity of these subjects. According to data from radiological survey conducted by the Global Fund Project and the National Tuberculosis Control Program (PNCT), the prevalence of tuberculosis at “Presídio Central”, a penitentiary, in 2011, is 9.1%, number that contributes to the city of Porto Alegre holding the title of capital with the highest incidence of cases in the country. The prisoner, when developing tuberculosis, gets a boost of stigmas by the prison system because the disease out of prison states a disqualified social identity. To understand the concept of identity, we use Antonio da Costa Ciampa’s theory (1998), understood here as Syntagma IdentityMetamorphosis-Emancipation. With regard to Recognition, we use Nancy Fraser’s proposal (2006), and the readings of Giorgio Agamben (2010) on the State of exception. The relevance of this research is associated with the ability to analyze the relation of identity constitution of prison egresses in relation to tuberculosis treatment and the factors that shape metamorphoses in the life trajectory of these subjects in the quest for recognition and empowerment strategies.
Keywords: Identidade; Tuberculose; Prisão; Reconhecimento; Identity; Tuberculosis; Prison; Recognition; ACCNPQ::Ciências Humanas::Sociologia